Congenital brachial plexus palsy. Issue 4 (April 2016) - Smith, Katherine; Patel, Vaishali
Abstract: Congenital brachial plexus palsy (CBPP) occurs secondary to traumatic injury to the brachial plexus in the perinatal period. It is a commonly encountered problem on the postnatal wards with the potential for significant morbidity. Previously termed 'obstetrical brachial plexus palsy', recent evidence suggests that it may occur independently of the actions of the birth attendant in some cases. Significant risk factors include shoulder dystocia, macrosomia, instrumental delivery and prolonged second stage of labour. Prognosis is variable and dependent on the type and level of nerve injury with total plexus palsies having the worst prognosis. Approximately two thirds of patients will have complete and spontaneous recovery by 6 months of age. However in those with residual defects, secondary complications may develop. It is important to diagnose it early and manage appropriately due to the risk of long term neuromuscular dysfunction and deformities in the affected arm in some cases. Management following recognition involves, prompt paediatric review and exclusion of associated injuries such as bony fractures. Urgent and regular physiotherapy input is crucial in preventing complications and monitoring progress. Primary surgical repair may be indicated in cases that do not or are unlikely to recover and prompt and early referral to a specialist centre is recommended in these difficult cases. Secondary surgery may also be indicated in those who develop complications. This review details the pathophysiology, risk factors and classification of CBPP. It suggests a systematic approach to the diagnosis of CBPP and gives a framework for understanding its management and prognosis.